THE CONCEPTS OF ISLAMIC PRODUCTION - DR, EFRITA NORMAN; MR, SAMSUL BASRI (Archives of Business Research, 2019)
Production was thought to play important role in economic activities. It was impossible to do other economic activities such as consumption, distribution or trading without the production itself. This study explained the concept of production in Islamic perspective. This study was purposed to give the explanation about the Islamic principles of production. The approach used in this study is a qualitative approach in the form of descriptive analysis. The use of qualitative approaches is deemed appropriate in reviewing this research because it aims to understand the concept of production in Islam. This type of data consists of general words and cases, written data sources, and analysis is qualitative research. The Qur'an and the hadith and some concepts regarding production in Islam are the main data sources. As the results in this study, described how the production concept is in accordance with Islamic teachings. In conventional term, production was limited as a process to make or create something, such as product, etc. It had placed profit over everything. On the other hand, in Islamic perspective, the production had been placed on the spirit of Islam itself. It contained fairness, benefit for either the producer or consumer.